Chromatin Remodelling - Radzioch, Danuta (IntechOpen, 2013)
The term "chromatin remodelling" is widely used to describe changes in chromatin structure which is controlled by histone-modifying enzymes, chromatin remodelling complexes, non-histone DNA-binding proteins and noncoding RNAs. Many human diseases such as cancer, various genetic syndromes, autism and infectious disease have been linked to the disruption of these control processes by genetic, environmental or microbial factors. Therefore, to unravel the mechanisms by which they operate is one of the most exciting and rapid developing fields of modern biology and will contribute to new ways in treatment of these diseases. The chapters in this book will focus on recent advances in our understanding of the mechanisms that govern the dynamic structural of chromatin, thereby providing important insights into gene regulation, DNA repair, and human diseases.